DIETARY CAPSAICIN AND IMMUNE SYSTEM - V, Sri Sreshtaa; rani. S, Leslie; M.P, Brundha; K, Anjaneyulu (International Journal of Psychosocial Rehabilitation, 2020)
Capsaicin is a chemical compound that was initially isolated from chili peppers in crystalline form. It was discovered that capsaicin caused a burning sensation in the mucous membranes of the oral cavity and the gastrointestinal tract. In addition, it increases the secretion of gastric acid and stimulates the nerve endings in the skinHot foods, such as peppers and sauces, contain an ingredient called capsaicin. Capsaicin can be a very effective pain reliever and is even used topically for neuropathy pain. Hot peppers can boost your immune system, helping to ward off germs that can cause illness. Capsaicin is an active component of immune System modulation and is an essential component of chilli peppers. They have also shown beneficial properties on organs in maintaining their health and condition Studies on capsaicin's and chilli peppers efficacy in modulating the immune system, its anti-inflammatory properties, maintaining organ health, and anti - carcinogen effects are collected and analysed. Besides having anticarcinogenic properties and killing tumor cells, capsaicin has been identified to have immune-modulating properties, being able to activate DCs through vanilloid receptor 1 (VR1). Previous studies showing its role in immunity, immune responses, and reducing insulin spikes in diabetes are focused on. The mechanism of action of capsaicin on the human immune system discussed . The study concludes by providing knowledge regarding the potential of capsaicin and its sale as a potent immune booster.